Karakteristik Kimia dan Sensoris Kue Gandus dengan Penambahan Daging Ikan Gabus (Channa striata) - Yunisah Yunisah; Herpandi Herpandi; Sabri Sudirman (Universitas Sriwijaya, 2022)
This study aimed to determine the effect of snakehead fish (Channa striata) meat addition with different concentrations on the chemical and sensory characteristics of the “gandus” cake. This research was conducted in laboratory experiments and by randomized block design with the different concentrations of snakehead fish meat (0%, 10%, 20% and 30%) with 3 replications. The parameters consist of chemical properties (moisture content, ash, protein, fat, and carbohydrate) and sensory analysis (texture, aroma and taste). The results showed that the different concentrations of snakehead fish meat addition had a significant effect on the moisture content, protein, fat and carbohydrate of the “gandus” cake. However, there is no significant affect on the ash content. The sensory analysis also showed a significant effect on texture, aroma, and taste. Therefore, the addition of snakehead fish meat has significant effects on the physicochemical and sensory characteristics of the “gandus” cake.